STRATEGI MENGHADAPI KONFLIK EMOSIONAL ORANG TUA - REMAJA - Sugiyatno Sugiyatno (Paradigma, 2009)
Adolescent phase have complex and unique characteristic, like; emotional labile, easy to hit by environmental influence, and not yet finding their self. The condition can overcome with giving optimal attention. Step early to give education and attention is understand characteristic of adolescent, know what wanted of adolescent, and later;then do approachs psychologically Workdload of parents have giving negative impact for adolescent behavior. Adolescent have losing of its rightss to get affection, not get attention, and sometimes their action cannot responbility, like fight, drunken, narcotic, action of asusila, impolite. and so on. This condition represent adolescent emotional conflict with parents which must be solved. Need wise, openness. and correct of stategi to finishing it.Keywords : parents, emotion, emancipation, adolescent, strategy, conflict